2019
DOI: 10.1016/j.idcr.2019.e00521
|View full text |Cite
|
Sign up to set email alerts
|

A case series of actinomycosis from a single tertiary care center in Saudi Arabia

Abstract: Actinomycosis is an uncommon but curable chronic infection caused by Actinomyces spp. The cervicofacial region is the most susceptible to infection; however, other sites may also become infected. Data on the current prevalence of this rare disease in Riyadh, Saudi Arabia is lacking. We herein report a case series of four patients with actinomycosis from a single tertiary care center in Riyadh, Saudi Arabia.Three patients presented to us with slowly progressing actinomycosis and one patient developed an acute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[11,12] Hence, physicians should be considered at the end of their differential diagnosis list and follow the pathology results to prevent misdiagnosis. [10,13,14] Antibiotic therapy is the conventional treatment of actinomycosis. High-dose i.v penicillin G (18-24 million units/day) for 2-6 weeks, followed by penicillin V or amoxicillin orally for 6-12 months, is suggested for treatment and relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Hence, physicians should be considered at the end of their differential diagnosis list and follow the pathology results to prevent misdiagnosis. [10,13,14] Antibiotic therapy is the conventional treatment of actinomycosis. High-dose i.v penicillin G (18-24 million units/day) for 2-6 weeks, followed by penicillin V or amoxicillin orally for 6-12 months, is suggested for treatment and relapse prevention.…”
Section: Discussionmentioning
confidence: 99%
“…That is because of the avascular fi brotic walls of the lesions (19,29,30), which maintains the anaerobic environment, stimulating the organisms' growth (11,31). Depending on disease severity, therapy may consist of high doses of penicillin G IV (10 to 20 million IU/day) for days or weeks, followed by oral penicillin V (2 to 4 g / day) for 3 to 12 months (13,17,(32)(33)(34).…”
Section: Treatmentmentioning
confidence: 99%
“…Microbiological studies on tonsils after tonsillectomies have shown that actinomyces colonize tonsillar crypts in 6.7%‐35% of samples 1,3 …”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by the formation of slightly painful pseudotumor of slow growth, which may progress into abscess and form fistulous tracts. Diseases associated with actinomycosis may also resemble malignancies, tuberculosis, and nocardiosis, often leading to misdiagnosis 2,3 …”
Section: Introductionmentioning
confidence: 99%